Tlingit women and children cleaning fish on beach, southeastern Alaska, ca.1907 - University of Washington Libraries
Three women and three small children cleaning fish around a canoe on rocky beach, ca. 1904-1910. Painted on rocks across water in background is the word 'Saloon' Caption on image: 468-a W&S Caption in album: The women here appear to be doing the work and attending to the business. The men are at the saloon, maybe, the sign of which shows. In Prosch Indian Album, v. 2, no. 42 Note from unidentifed source: Southeastern Alaska - Tlingit?